Preventing Corruption in Higher Education in Macedonia through Whistle-Blowing: Lessons Learned - Dokmanovikj, Misho ; Spasevski, Darko; Shapkova Kocevska, Katerina (Institute for Strategic Research and Education, 2018)
Recent study has showed that there is high perception of corruption among students and university employees in Macedonia. The Law on Whistleblowers’ Protection has not been implemented at many universities as they lack effective procedures for preventing corruption including appointment of authorized individuals for reporting corruption. This paper presents the lessons learned from the implementation of “Corruption Free University Project”, a 12 months long project of the Institute for Strategic Research and Education (ISIE) with regard to findings about corruption in higher education in Macedonia and implementation of the Law on Whistleblowers’ Protection in the academic sector.